Atypical early presentation of subacute sclerosing panencephalitis in children: A case series - Sukanya Nath; Kanai Lal Barik; Abu Obayed; Laha, Sumanta; Sayan Bera (Asian Journal of Medical Sciences, 2023)
Subacute sclerosing panencephalitis (SSPE) is a progressive neurodegenerative disease of children and young adults that may occur as an uncommon complication 7–10 years after a measles infection. In measles – endemic countries like India, the incidence of this fatal disease is high and more number of new cases are detected in recent times. In this case series, we have presented three cases of SSPE between the 4 and 5 years age group, presented with abnormal movement and neuroregression and diagnosed by characteristic clinical features, raised anti-measles antibody titer in CSF, and typical Electroencephalography findings. All of them had a history of measles infection before the vaccination and very short latency period between measles infection and the development of SSPE. They were discharged in stable condition after the treatment with oral Isoprinosine and intrathecal Interferon alfa 2b. Early age of presentation, short latency period, and apparently good response to treatment for the time being prompted us to present these cases.